Pengaruh Persepsi Risiko dan Kepercayaan Terhadap Keputusan Menabung Emas pada Ibu Rumah Tangga dengan Persepsi Manfaat Investasi Emas Sebagai Variabel Moderating - Sehani Sehani (Al-Manar Journal of Accountancy and Business Studies, 2025)
This study aims to determine the influence of risk perception and trust partially and simultaneously on the decision to save gold among housewives in Pekanbaru City and to determine whether the perception of the benefits of gold investment can moderate the relationship between risk perception and trust with the decision to save gold among housewives in Pekanbaru City. The types and sources of data for this study consist of primary and secondary data. Primary data is research data obtained directly from research respondents. Secondary data is reference data related to the research study. Data analysis techniques used multiple regression and multiple regression models with a moderating interaction test. The results of the study are that partially and simultaneously risk perception and trust have a positive and significant effect on the decision to save gold among housewives in Pekanbaru City. The variable of perceived benefits is a moderating variable that strengthens the relationship between risk perception and trust on the decision to save gold among housewives in Pekanbaru City.